Detection and characterization of silencers and enhancer-blockers in the greater CFTR locus - Petrykowska, Hanna M.; Vockley, Christopher M.; Elnitski, Laura (Genome Research, 2008)
Silencers and enhancer-blockers (EBs) are cis-acting, negative regulatory elements (NREs) that control interactions between promoters and enhancers. Although relatively uncharacterized in terms of biological mechanisms, these elements are likely to be abundant in the genome. We developed an experimental strategy to identify silencers and EBs using transient transfection assays. A known insulator and EB from the chicken beta-globin locus, cHS4, served as a control element for these assays. We examined 47 sequences from a 1.8-Mb region of human chromosome 7 for silencer and EB activities. The majority of functional elements displayed directional and promoter-specific activities. A limited number of sequences acted in a dual manner, as both silencers and EBs. We examined genomic data, epigenetic modifications, and sequence motifs within these regions. Strong silencer elements contained a novel CT-rich motif, often in multiple copies. Deletion of the motif from three regions caused a measurable loss of silencing ability in these sequences. Moreover, five duplicate occurrences of this motif were identified in the cHS4 insulator. These motifs provided an explanation for an uncharacterized silencing activity we measured in the insulator element. Overall, we identified 15 novel NREs, which contribute new insights into the prevalence and composition of sequences that negatively regulate gene expression.